4(8-c)=8c+16-6c

Simple and best practice solution for 4(8-c)=8c+16-6c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(8-c)=8c+16-6c equation:


Simplifying
4(8 + -1c) = 8c + 16 + -6c
(8 * 4 + -1c * 4) = 8c + 16 + -6c
(32 + -4c) = 8c + 16 + -6c

Reorder the terms:
32 + -4c = 16 + 8c + -6c

Combine like terms: 8c + -6c = 2c
32 + -4c = 16 + 2c

Solving
32 + -4c = 16 + 2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-2c' to each side of the equation.
32 + -4c + -2c = 16 + 2c + -2c

Combine like terms: -4c + -2c = -6c
32 + -6c = 16 + 2c + -2c

Combine like terms: 2c + -2c = 0
32 + -6c = 16 + 0
32 + -6c = 16

Add '-32' to each side of the equation.
32 + -32 + -6c = 16 + -32

Combine like terms: 32 + -32 = 0
0 + -6c = 16 + -32
-6c = 16 + -32

Combine like terms: 16 + -32 = -16
-6c = -16

Divide each side by '-6'.
c = 2.666666667

Simplifying
c = 2.666666667

See similar equations:

| 28=(x-.5)+9 | | 28x+12y=8 | | 8y/6+3/6=5y/6 | | -39+8m=-5(1-5m) | | 10-9v+v= | | 5+3(2x-4)=9-4+(3x+1) | | 6*26= | | 3n+n=236 | | 5x+7x-38=95-7x | | x^2+3x+14=24 | | (3x^2)+2x-15=0 | | -7y+2=5y-7 | | y^2-3=y+9 | | 2(4x-4)+2(3x-2)=360 | | 21x^2-18x^3=6x | | -56=-49t | | 7x-4y=-26 | | 7x-2(4-3x)=3(2x+1) | | 5+7x-3x=-27 | | 3x+w=8x+v | | 53350-75h+200h=55825-150h | | 2n(n+5)= | | 7.2y+3=3y+21 | | 6-6x-3=-46+3x-14 | | -3x^2+246x-1100=0 | | 200M-75m+53350=55825-150m | | a^2+3a= | | 2e+2.6=-23 | | 7(9w)= | | 6(v+4)-2v=2(2v+1)-7 | | X+6-4x=21 | | (3x-10)+(x+40)=90 |

Equations solver categories